The Effect of STEM-PJBL Model on Students' Creative Thinking Skills - Mutia Rahman, Zahra; Muttaqin, Arief; Evita Putri, Rahmah (UNIVERSITAS NEGERI MEDAN, 2025)
Creative thinking is one of the essential 21st-century skills required to respond to rapid global change. The STEM-PjBL (Science, Technology, Engineering, and Mathematics–Project-Based Learning) model integrates project-based learning with STEM principles, thereby fostering students’ creativity and interdisciplinary understanding. This qualitative literature review analyzed 14 research articles selected through purposive sampling using Google Scholar, with inclusion criteria focusing on studies examining the influence of STEM-PjBL on creative thinking. The review findings consistently indicate that STEM-PjBL enhances students’ ability to generate ideas, solve problems, and engage in higher-order thinking processes. These results confirm that STEM-PjBL is an effective instructional model to strengthen creative thinking as a 21st-century competence.